Chrom3D: three-dimensional genome modeling from Hi-C and nuclear lamin-genome contacts. Issue 1 (December 2017) - Paulsen, Jonas; Sekelja, Monika; Oldenburg, Anja; Barateau, Alice; Briand, Nolwenn; Delbarre, Erwan; Shah, Akshay; Sørensen, Anita; Vigouroux, Corinne; Buendia, Brigitte; Collas, Philippe
Abstract Current three-dimensional (3D) genome modeling platforms are limited by their inability to account for radial placement of loci in the nucleus. We present Chrom3D, a user-friendly whole-genome 3D computational modeling framework that simulates positions of topologically-associated domains (TADs) relative to each other and to the nuclear periphery. Chrom3D integrates chromosome conformation capture (Hi-C) and lamin-associated domain (LAD) datasets to generate structure ensembles that recapitulate radial distributions of TADs detected in single cells. Chrom3D reveals unexpected spatial features of LAD regulation in cells from patients with a laminopathy-causing lamin mutation. Chrom3D is freely available on github.